Association of the Total White Blood Cell, Neutrophils, and Monocytes Count With the Presence, Severity, and Types of Carotid Atherosclerotic Plaque - Liu, Yanhua; Zhu, Yongjian; Jia, Wenrui; Sun, Dan; Zhao, Li; Zhang, Chen; Wang, Cuicui; Lyu, Quanjun; Chen, Yuming; Chen, Gaiyun; Bo, Yacong; Xing, Yurong (Frontiers in Medicine, 2020)
Background: White blood cells have established inflammatory and immunologic function, and may contribute to the pathophysiology of atherosclerosis. Methods: A cross-sectional study included 3,569 healthy Chinese adults was conducted between Jan 2016 and Dec 2018 in Zhengzhou, China. Fasting peripheral venous blood was collected for analyze of the total white blood cell (WBC) count and WBC subtypes. The size, composition and types of carotid atherosclerotic plaques (CAPs) in the common carotid artery, the internal carotid artery, and the external carotid artery were measured bilaterally using B-mode ultrasound. Results: After adjustting for potential confounding factors, total WBC, neutrophils and monocytes count showed significant associations with the presence of CAPs in men but not in women, with the odds ratios (95% CI) in the highest (versus the lowest) quartile 1.99 (1.33-2.97), 1.65 (1.10-2.47), and 2.17 (1.41-3.18) (P-trend = 0.004, P-trend = 0.004 and P-trend < 0.001) respectively. The three leukocyte counts were also significantly positively associated with the severity of carotid atherosclerosis, as judged by the sum of CAPs, the maximal internal carotid plaque thickness and plaque score (all P < 0.01, P-trend < 0.05). Compared with individuals without CAPs, those with echolucent plaques had significantly increased total WBC and neutrophil counts, whereas those with polytype plaques had a significantly increased monocyte count. Conclusion: WBC, neutrophils and monocytes count were significantly associated with the presence, severity and types of CAPs in a healthy Chinese population.